منهج الشيخ نووي الجاوي في تفسيره وإسهاماته في تدوين العلوم الشرعيّة (دراسة موضوعية) - Muhammad Firdaus; Fitriana Rusyai Ali Ahmad (Al-Muyassar: Journal of Arabic Education, 2022)
This study attempts in a modest manner to identify the personality of Sheikh Nawawi Al-Jawi with a presentation of his interpretation method “Marah Labid li Kasyfi Ma’na Qur’an Majid”, and to know his role and contributions in the field of codifying Islamic sciences, which makes Sheikh Nawawi Al-Jawi called the master of Hijaz scholars. This study aims to identify Sheikh Nawawi Al-Jawi and his writings, and the approach taken by the Sheikh in his interpretation known as Marah Labid li Kasyfi Ma’na Qur’an Majid. The importance of this research is to identify the finest methods for activating the sharia sciences in the books of Sheikh Nawawi Al-Jawi and his method of interpretation. The research method that the researcher depends on is library research, and this is done by tracking the interpretation of the Sheikh and his writings, with the help of other modern references from books of interpretations, hadiths and others, in order to know his contributions in the field of codification of sharia sciences.